The Pattern of Inheriting Expertise in the Aligo Nasheed Group - Muh. Kurniawan Adi Kusuma Wiharja; Wadiyo Wadiyo; Yudi Sukmayadi; Slamet Haryono (International Conference on Science, Education, and Technology, 2023)
Nasheed music is a type of music that is rich in Islamic values conveyed through its lyrics. One of the nasheed groups in Makassar City is the Aligo nasheed group. This group has been active for approximately 16 years and is influential in Makassar City. This research aims to gain an understanding of the cultural inheritance process within the Aligo nasheed group, using the Cavalli Sforza and Feldman cultural inheritance framework and qualitative methods. The research findings indicate that there is a cultural inheritance process in the learning activities conducted by the Aligo nasheed group. This inheritance process occurs horizontally among group members during weekly practice sessions. The exchange of information and nasheed knowledge takes place during these group practice sessions.